Vector form intrinsic finite element analysis of the construction process of cable–strut–beam steel structures. Issue 7 (July 2016) - Zhu, ML; Lu, JY; Guo, ZX; Dong, SL
The construction process is a time-consuming and dynamic process subject to a changing environment. The time and path influence should be considered for a more exact result on its mechanical behavior, especially for large-span spatial structures. This article presents a structural analysis framework called the vector form intrinsic finite element for construction simulations. The vector form intrinsic finite element based on vector mechanics is different from the traditional finite element method, which is developed from continuum mechanics. It is easy to solve problems involving nonlinearity without establishing the equilibrium matrix. The construction process, such as erection of cables, is accompanied by mechanisms and rigid body motions. Furthermore, a new element, named the traction cable element, is proposed to analyze the lifting process, and the expression of the internal element force is derived. The results obtained from the lifting of a single cable illustrate that vector form intrinsic finite element can produce an accurate analysis result. Finally, analysis of a practical project shows the capability of vector form intrinsic finite element in the construction simulation of a cable–strut–beam steel structure.